Cytotoxic effects of 4′-hydroxychalcone on human neuroblastoma cells (SH-SY5Y). (December 2019) - de Moura Escobar, Stephane Janaina; Simone, Martin; Martin, Nathan; de Oliveira Ribeiro, Ciro Alberto; Martinez, Glaucia Regina; Winnischofer, Sheila Maria Brochado; Witting, Paul Kenneth; Rocha, Maria Eliane Merlin
Abstract: Neuroblastoma is an aggressive form of cancer with high mortality. Hydroxychalcones have received considerable attention because of their cytotoxic activities on cancer cells. However, the effect of the 4′-hydroxychalcone on neuroblastoma cells is unknown. The aim of the present study was to characterize the cytotoxicity of 4HC to neuroblastoma and the importance of mitochondrial effects in its action mechanism using an in vitro model of SH-SY5Y cells. Incubation of cultured SHSY5Y cells with 10–60 μM 4HC (24 h) decreased cell confluency, cellular metabolic activity and depleted intracellular ATP relative to the vehicle-treated control. The mechanism of 4HC-induced cell toxicity likely involves mitochondria dysfunctional as judged by inhibition of mitochondrial respiration, depolarization of mitochondria membrane potential and intracellular and morphological alterations. Furthermore, loss of cell viability was accompanied mainly by increase of phosphatidylserine exposure on the surface of cells, suggesting that the flavonoid may induce apoptosis in SH-SY5Y cells. In addition, treatment inhibited SH-SY5Y cell migration/proliferation in a scratch assay and induced significant changes in the cell cycle progression. Our results showed the effects of 4HC in the human neuroblastoma cell line SH-SY5Y are associated with mitochondrial dysfunctional, depletion of intracellular ATP levels, ROS increase, alteration in cell cycle progression and cellular morphology. Highlights: 4′-hydroxychalcone decreases the viability of neuroblastoma SH-SY5Y cells. 4′-hydroxychalcone promote alteration in cell cycle progression. Cellular morphological changes, ROS increase and mitochondrial alterations occur after 4′-hydroxychalcone treatment.